Neurons and cardiomyocytes derived from induced pluripotent stem cells as a model for mitochondrial defects in Friedreich's ataxia - Aurore Hick; Marie Wattenhofer-Donzé; Satyan Chintawar; Philippe Tropel; Jodie P. Simard; Nadège Vaucamps; David Gall; Laurie Lambot; Cécile André; Laurence Reutenauer; Myriam Rai; Marius Teletin; et al. (The Company of Biologists, 2013)
SUMMARY Friedreich's ataxia (FRDA) is a recessive neurodegenerative disorder commonly associated with hypertrophic cardiomyopathy. FRDA is due to expanded GAA repeats within the first intron of the gene encoding frataxin, a conserved mitochondrial protein involved in iron-sulphur cluster biosynthesis. This mutation leads to partial gene silencing and substantial reduction of the frataxin level. To overcome limitations of current cellular models of FRDA, we derived induced pluripotent stem cells (iPSCs) from two FRDA patients and successfully differentiated them into neurons and cardiomyocytes, two affected cell types in FRDA. All FRDA iPSC lines displayed expanded GAA alleles prone to high instability and decreased levels of frataxin, but no biochemical phenotype was observed. Interestingly, both FRDA iPSC-derived neurons and cardiomyocytes exhibited signs of impaired mitochondrial function, with decreased mitochondrial membrane potential and progressive mitochondrial degeneration, respectively. Our data show for the first time that FRDA iPSCs and their neuronal and cardiac derivatives represent promising models for the study of mitochondrial damage and GAA expansion instability in FRDA.